Pengaruh Metode Penugasan Pekerjaan Rumah Terhadap Hasil Belajar Matematika Kelas V - Ani Fatul Munawaroh; Oky Ristya Trisnawati; Atim Rinawati (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to determine how the effect of the homework assignment method on themathematics learning outcomes of class V MI Ma'arif Jatimulyo. This research is a PreExperimental Design with the type of one-Group Pretest-Posttest Design. The population inthis study were all fifth grade students at MI Ma'arif Jatimulyo. The sampling technique usedwas saturated sampling. Data collection techniques in this study were observation, interviews,tests and documentation. The data analysis technique used in this research is using t-testthrough SPSS 26.0 Software. Based on the results of the research and discussion obtained, itcan be seen from the results of the data that has been carried out using pretest and posttestquestions. Based on the results of the T-test data processing with SPSS 26.0 Software, it canbe seen that the value of siq = 0.000. The value siq < 0.05, then Ho is rejected. So, there is aneffect of the homework assignment method on student learning outcomes in mathematicslearning for class V MI Ma'arif Jatimulyo